Computer simulation of hydraulic system of exoskeleton - Г.К. Боровин Borovin, G. К. (2020)
Exoskeleton is a device, which is put on a human and is intended for human's augmentation, in particular, to increase the efforts that a person may apply. Application of this system may be useful during execution of heavy works such as cargo handling works, in places where there is no opportunity of application of wheel loaders, and repair works on heavy objects. As the actuators of joints of exoskeleton, it is most logical to use hydraulic drives as they have a number of advantages in comparison with electrical and pneumatic actuators. Important among them are high speed and high specific capacity (torque to weight ratio) that allows designing a more compact drive. As an energy source, an internal combustion engine may be considered.